2015
DOI: 10.4103/0366-6999.149219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutamine Enriched Nutrition Support on Surgical Patients with Gastrointestinal Tumor

Abstract: Background:Associations between glutamine (Gln) enriched nutrition support and surgical patients with gastrointestinal (GI) tumor remain controversy. The purpose of this meta-analysis was to assess the effect of Gln enriched nutrition support on surgical patients with GI tumor in term of relevant biochemical indices, immune indices, and clinical outcomes.Methods:Six databases were systematically searched to find eligible randomized controlled trials (RCTs) from 1966 to May 2014. When estimated the analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Increased serum levels of hs-CRP observed after exhaustive exercise in our study is in line with findings of the study by Vincent et al43 Inflammatory reaction in intensive exercise has been reported as one of the reasons for sport injury 44. Glutamine may play a role in improving and controlling inflammatory processes 45. Thus, in this study, the reduction of the inflammatory process as a result of glutamine supplementation is considered a very important finding because it can prevent sport damage associated with increased inflammation in sport and glutamine consumption can be beneficial for young healthy males performing intense physical activities.…”
Section: Discussionsupporting
confidence: 92%
“…Increased serum levels of hs-CRP observed after exhaustive exercise in our study is in line with findings of the study by Vincent et al43 Inflammatory reaction in intensive exercise has been reported as one of the reasons for sport injury 44. Glutamine may play a role in improving and controlling inflammatory processes 45. Thus, in this study, the reduction of the inflammatory process as a result of glutamine supplementation is considered a very important finding because it can prevent sport damage associated with increased inflammation in sport and glutamine consumption can be beneficial for young healthy males performing intense physical activities.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, an improvement of immune parameters has been emphasized in a recent meta-analysis by Kang et al on 13 RCTs including 1034 surgical patients with gastrointestinal tumour. In three of the studies glutamine was administered via the enteral route [275] (1þ). Another meta-analysis included 19 RCTs with 1243 patients.…”
Section: Commentarymentioning
confidence: 99%
“…12, 19-20 Some authors reported that supplementation of enteral or parenteral glutamine showed improved immune function, reduced infections, and shortened the length of ICU stay. [29][30][31] Day 1 SOFA score is an indicator of the severity of illness. The decrease in SOFA score was statistically significant in the two groups.…”
Section: Discussionmentioning
confidence: 99%